Efficacy and Safety of Dupilumab in Chinese Patients With Atopic Dermatitis: A Real-World Study - Zhou, Bingjing; Peng, Cong; Li, Liqiao; Liu, Runqiu; Zhu, Lei; Chen, Xiang; Li, Jie (Frontiers in Medicine, 2022)
Background: Atopic dermatitis (AD) is a common skin disease, but treatment of this disease has been challenging. Dupilumab is a new biological agent for AD that has been proven to be safe and effective in clinical trials. Although dupilumab was approved for listing in China in June 2020, real-world data about the application of dupilumab in China are lacking. This study aimed to collect and analyse real-world data on dupilumab among Chinese AD patients. Methods: Demographic and clinical data for 116 AD patients receiving dupilumab treatment were reviewed. The Eczema Area and Severity Index (EASI), SCORing Atopic Dermatitis (SCORAD), Numerical Rating Scale (NRS), Patient Oriented Eczema Measure (POEM), and Dermatology Quality of Life Index (DLQI) of patients were evaluated every two weeks from baseline to 16 weeks of treatment. Any adverse events during treatment were recorded. Results: Among the 116 patients in this study, baseline levels of IgE, eosinophils and LDH were elevated in 62.79% (n=86), 45.30% (n=86) and 54.20% of patients (n=48), respectively. The SCORAD index and POEM, DLQI and NRS scores were significantly improved in all patients at 2 weeks (p<0.0001),4 weeks (p<0.01) and 16 weeks (p<0.001). EASI scores also improved significantly in all patients at 2 weeks (p<0.01), 4 weeks (>0.05) and 16 weeks (p<0.01). However, 11 patients (9.48%) had no response. IgE and LDH levels (p>0.05), Eosinophil counts (p<0.01) in blood increased temporarily in the first 4 weeks and then decreased and stabilized during dupilumab treatment. Conjunctivitis was the most common adverse event (2.59%) among the patients. We found that the curative efficacy of dupilumab at 4th weeks was related to the patient’s age and course of disease. Nevertheless, there is no relationship between levels of eosinophils, IgE, LDH and the therapeutic efficacy of dupilumab. Conclusions: The real-world data in China showed that dupilumab can effectively treat AD and is well tolerated with a low incidence of adverse events.